Advances in Manufacturing and Characterization of Functional Polyesters - Balart Gimeno, Rafael Antonio; Montañés Muñoz, Nestor; Torres-Giner, Sergio; Boronat Vitoria, Teodomiro; Fenollar Gimeno, Octavio Ángel (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In recent years, we have assisted the remarkable growth in the use of functional polyesters. This book gathers novel research works dealing with the manufacturing and characterization of polyesters that have been functionalized by synthesis, copolymerization, additives (at micro- and nanoscale), surface modification, among other methodologies, to tailor desired properties in terms of mechanical, chemical, thermal, and barrier properties, biodegradation, and biocompatibility. Thus, Advances in Manufacturing and Characterization of Functional Polyesters will serve to guide a diverse audience of polymer scientists and engineers and provides an update of the "state-of-the-art" knowledge on functional polyesters.